Watch-and-wait approach versus surgical resection after chemoradiotherapy for patients with rectal cancer (the OnCoRe project): a propensity-score matched cohort analysis. Issue 2 (February 2016) - Renehan, Andrew G; Malcomson, Lee; Emsley, Richard; Gollins, Simon; Maw, Andrew; Myint, Arthur Sun; Rooney, Paul S; Susnerwala, Shabbir; Blower, Anthony; Saunders, Mark P; Wilson, Malcolm S; Scott, Nigel; et al.
Summary: Background: Induction of a clinical complete response with chemoradiotherapy, followed by observation via a watch-and-wait approach, has emerged as a management option for patients with rectal cancer. We aimed to address the shortage of evidence regarding the safety of the watch-and-wait approach by comparing oncological outcomes between patients managed by watch and wait who achieved a clinical complete response and those who had surgical resection (standard care). Methods: Oncological Outcomes after Clinical Complete Response in Patients with Rectal Cancer (OnCoRe) was a propensity-score matched cohort analysis study, that included patients of all ages diagnosed with rectal adenocarcinoma without distant metastases who had received preoperative chemoradiotherapy (45 Gy in 25 daily fractions with concurrent fluoropyrimidine-based chemotherapy) at a tertiary cancer centre in Manchester, UK, between Jan 14, 2011, and April 15, 2013. Patients who had a clinical complete response were offered management with the watch-and-wait approach, and patients who did not have a complete clinical response were offered surgical resection if eligible. We also included patients with a clinical complete response managed by watch and wait between March 10, 2005, and Jan 21, 2015, across three neighbouring UK regional cancer centres, whose details were obtained through a registry. For comparative analyses, we derived one-to-one paired cohorts of watch and wait versus surgical resection using propensity-score matching (including T stage, age, and performance status). The primary endpoint was non-regrowth disease-free survival from the date that chemoradiotherapy was started, and secondary endpoints were overall survival, and colostomy-free survival. We used a conservative p value of less than 0·01 to indicate statistical significance in the comparative analyses. Findings: 259 patients were included in our Manchester tertiary cancer centre cohort, 228 of whom underwent surgical resection at referring hospitals and 31 of whom had a clinical complete response, managed by watch and wait. A further 98 patients were added to the watch-and-wait group via the registry. Of the 129 patients managed by watch and wait (median follow-up 33 months [IQR 19–43]), 44 (34%) had local regrowths (3-year actuarial rate 38% [95% CI 30–48]); 36 (88%) of 41 patients with non-metastatic local regrowths were salvaged. In the matched analyses (109 patients in each treatment group), no differences in 3-year non-regrowth disease-free survival were noted between watch and wait and surgical resection (88% [95% CI 75–94] with watch and wait vs 78% [63–87] with surgical resection; time-varying p=0·043). Similarly, no difference in 3-year overall survival was noted (96% [88–98] vs 87% [77–93]; time-varying p=0·024). By contrast, patients managed by watch and wait had significantly better 3-year colostomy-free survival than did those who had surgical resection (74% [95% CI 64–82] vs 47% [37–57]; hazard ratio 0·445 [95% CI 0·31–0·63; p<0·0001), with a 26% (95% CI 13–39) absolute difference in patients who avoided permanent colostomy at 3 years between treatment groups. Interpretation: A substantial proportion of patients with rectal cancer managed by watch and wait avoided major surgery and averted permanent colostomy without loss of oncological safety at 3 years. These findings should inform decision making at the outset of chemoradiotherapy. Funding: Bowel Disease Research Foundation.